Buddhism in Muslim Indonesia - Steenbrink, Karel (Studia Islamika, 2013)
This article presents an overview of various ways in which Buddhists and Muslims have lived together in Indonesia since the arrival of Islam about 1200. It tells how Buddhism has slowly disappeared and become a religion for mainly the Chinese who, until the late 19th century, have often converted to Islam. This article analyzes the role of three key figures in the recent government–supported revival of Buddhism. These figures are the Chinese–Indonesian monk Ashin Jinarakkhita, the Balinese lay devotee and government official Oka Diputhera, and the Chinese–Indonesian businesswoman Sri Hartati Murdaya. They have tried to accommodate Buddhism to the Muslim–dominated nationalism of modern Indonesia. The result of the past five decades is that Buddhism has obtained a modest but safe position in independent Indonesia.DOI: 10.15408/sdi.v20i1.346